The Crusades : the authoritative history of the war for the Holy Land - Asbridge, Thomas S. (Ecco Press, 2010)
Drawing on painstaking original research and an intimate knowledge of the Near East, Thomas Asbridge uncovers what drove Muslims and Christians alike to embrace the ideals of "jihad" and crusade, revealing how these holy wars reshaped the medieval world and why they continue to influence events today.